Evaluation of Indigenous Strains of Entomopathogenic Nematodes, in Combination with Low-Toxicity Insecticides for Control of Fall Armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera, Noctuidae) - Kasi, Indra Kumar; Waiba, Kanchhi Maya; Singh, Gurveer; Bhat, Abhishek; Kashyap, Hemanth Kumar; Rostami, Elahe; Robin (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted during November, 2021 to evaluate the efficacy of local strains of Steinernema feltiae and Heterorhabditis bacteriophora in combination with low-toxicity insecticides at low and high dosages to control fifth-instar larvae in under laboratory condition. The experimental location in Department of Entomology, Nematology Laboratory, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Solan, Himachal Pradesh, India. The use of S. feltiae+Spinosad or chlorantraniliprole caused larvae mortality of over 90% at 96 h and H. bacteriophora+Spinosad or Chlorantraniliprole mortality caused of over 95% mortality at 96 h after treatment at the high dose and may be considered as a least toxic strategy to control fall armyworm. Our results showed that these strains of H. bacteriophora have high pathogenicity against S. frugiperda and have potential for biological control in integrated approaches causing even combination with low-toxicity insecticides at low and high dosages may be considered 90% mortality fifth instar larval of S. frugiperda at 96 h at the high dose as a least toxic strategy to control fall armyworm. The use of S. feltiae+Spinosad or chlorantraniliprole and H. bacteriophora+Spinosad or chlorantraniliprole caused larvae mortality of over 90% high dose and should be included as a least toxic strategy to control fall armyworm. Native strains of entomopathogenic nematodes are active against S. frugiperda shows potential alternative to the severe use of chemical insecticides to control fall armyworm population in corn plantations.